Zoning ofCheshmeh Gerdoo River of Noshahr with NSFWQI Index in Autumn 1391 - Hamid Reza Nassehinia; Gholamreza Ghaeni; Yousof Dadban Shahamat (Mazandaran University of Medical Sciences, 2015)
Introduction & Purpose:Population growthandpollutions caused bythe dischargeof sewageandagriculturalwasteleachatehas increased surface runoffsandgroundwaterscontaminationand it haslimitedwater resources. The zoning ofriver waterquality is thefirstand the most importantstepin themanagementof water resources. Because it makes clear theanalyst's viewoftheprocessandhowpollutionchangesovertime, andplacecertain conditions. Given theimportance of theCheshmeGerdooriverin thesupplyof drinking waterhanging over theNoshahrcityas well asmultiplepollutantsdischargedtothe river's waterquality assessmentin terms of healthisveryimportant. Methods:Inthisstudy, during the3 monthsto 6stationswere sampled. Quality parameterswere examinedalong the river. Thedatawereanalyzedusingqualitativeindicators. Quality parametersDO, BOD, Fecal coliform, NO3, PO4, TS, Turbidity, Temperatureand pHwere examinedalong the river. ThedatawereanalyzedusingNSFWQI quality indices. Results:Inthisstudy,the lowestDO quantity wasequal to6.4 mg/lat station6andthe maximumwasequal to8.5 mg/latstation1. Other parameterswereincreased. Therefore,in accordancewiththe results obtainedin thisriver,NSFWQIindexwas calculatedat the bestand atworst54.85 and39.19. Therefore,thequality indexofwaterintheriverabove in the station1 wasaverageandcategoryin the stations4,5,6wasbad. Conclusion:Fecal coliform and BODlevelsinthe riveratvarious pointsincreasedfrombeginning to end whichrepresents an increase ofpollution anditcan bedue tothe passage ofthe river fromboth rural and urbancentersand receiving of sewagewithout treatment.ParametersNO3, PO4havealsoincreasedthat canbe associatedwaterpollutioninriver withagricultural waste water.TSandTurbidityalsoincreasedfrom beginningtoendwhich can berelated to theabsence ofsuspended solidsdepositedalong theriver.